Erratum: Cooling in the Shade of Warped Transition Disks (Monthly Notices of the Royal Astronomical Society: Letters 2020 491 l17 - Perez-Marquez, S (Oxford University Press, 2020)
This is an Erratum to the paper Cooling in the shade of warped transition disks that was published in MNRAS, 486, L58-L62 (2019). The x-axis of Fig. 1 in the original version of the paper is incorrectly labeled, the temperature range of the grid for the Rosseland opacities should start at 10K, not 1K. Here we provide the correct version in Fig. 1 of this Erratum. This is a typographical error that does not impact on the calculations reported in the original paper. (Figure Presented). © 2019 The Author(s).